Peptide Ligands Specific to the Oxidized Form of Escherichia coli Thioredoxin - Scholle, Michael D. (Biochim Biophys Acta, 2008)
Thioredoxin (Trx) is a highly conserved redox protein involved in several essential cellular processes. In this study, our goal was to isolate peptide ligands to Escherichia coli Trx that mimic protein-protein interactions, specifically the T7 polymerase-Trx interaction. To do this, we subjected Trx to affinity selection against a panel of linear and cysteine-constrained peptides using M13 phage display. A novel cyclized conserved peptide sequence, with a motif of C(D/N/S/T/G)D(S/T)-hydrophobic-C-X-hydrophobic-P, was isolated to Trx. These peptides bound specifically to the E. coli Trx when compared to the human and spirulina homologs. An alanine substitution of the active site cysteines (CGPC) resulted in a significant loss of peptide binding affinity to the Cys-32 mutant. The peptides were also characterized in the context of Trx’s role as a processivity factor of the T7 DNA polymerase (gp5). As the interaction between gp5 and Trx normally takes place under reducing conditions, which might interfere with the conformation of the disulfide-bridged peptides, we made use of a 22 residue deletion mutant of gp5 in the thioredoxin binding domain (gp5Δ22) that bypassed the requirements of reducing conditions to interact with Trx. A competition study revealed that the peptide selectively inhibits the interaction of gp5Δ22 with Trx, under oxidizing conditions, with an IC50 of ~10 µM.